Efeito do trimetafosfato de sódio e do fluoreto sobre a solubilidade da hidroxiapatita: estudo in vitro - Souza, José Antonio Santos [UNESP] (2014)
The aim of this study was to evaluate the effect of different concentrations of sodium trimetaphosphate (TMP) associated with fluoride (F) on hydroxyapatite (HA) solubility, as well as in chemical and physical properties of HA after a pH-cycle. Synthetic HA powder (1.0 g; n= 6) was mixed with solutions of TMP at 0, 0.1, 0.2, 0.4, 0.6, 0.8, 1.0, 2.0, 4.0, 6.0, 8.0 and 10%, associated with fluoride at 0, 100, 250 and 500 ppm F, during 2 min. The suspension was filtered and the precipitates were dried for 24 h at 37°C and grinded. After the treatment, HA samples were submitted to a pH-cycle. Post-cycled HA samples were analyzed by energy-dispersive X-ray spectroscopy (EDX), infrared spectroscopy (FTIR) and X-ray diffraction (XRD). Afterwards, the concentration of alkali and acid soluble F, Ca and P were determined in post-cycled HA, as well as P and F in the supernatant. The data of F, Ca, P, Ca/P ratio of HA, and F and P in the supernatant were submitted to ANOVA and Student-Newman-Keuls' test (p<0.05). A reduction of the size of the HA crystallites was seen with increasing TMP concentrations in the solutions. HA treated with 500 ppm F and 1% TMP produced an HA with crystallites of larger size. The FTIR showed a reduction in the bands corresponding to phosphates and to carbonate for all groups when compared to the HA synthetized. The highest Ca/P ratios were observed for HA treated with TMP concentrations between 0.4% and 0.8% when combined with 250 ppm F, and between 0.4% and 2% in association with 500 ppm F (p<0.05). The increase of TMP led a reduced acid-soluble F incorporation in HA for all groups, both immediately after treatment and after the pH cycle (p<0.05). Additionally, the increase in TMP concentrations led to higher P adsorption to HA for the 0 and 100 ppm F solutions, but lower for...